MANFAAT MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KETERAMPILAN BERBICARA SISWA - Suhaimah, Annisa (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2023)
The writing of this article was written based on the lack of speaking skills of elementary school students who are less than optimal. The method used in writing this article is a qualitative method based on library research. The author examines the problem of language skills in students. Until now, students still feel unsure to express their opinions about the learning material they learn. When asked to speak in front of the class they tend to be shy, less expressive and mistaken about what they want to say. The findings of each article analyzed showed that the application of the jigsaw-type cooperative learning model had an influence on students' speaking skills. This is because the jigsaw model makes it easier for students to cooperate and exchange opinions with peers in preparing learning materials, the jigsaw model requires all students to equate mindset as the basis for delivery in discussion groups. Keywords: Speeking Skills; Jigsaw; Cooperative Learning Model.